An inhibitor of 11-β hydroxysteroid dehydrogenase type 1 (PF915275) alleviates nonylphenol-induced hyperadrenalism and adiposity in rat and human cells - Ling-Ling Chang; Wan-Song Alfred Wun; Paulus S. Wang (BMC, 2018)
Abstract Background Nonylphenol (NP) is an environmental endocrine-disrupting chemical (EDC) detected in human cord blood and milk. NP exposure in developmental periods results in hyperadrenalism and increasing 11β-hydroxysteroid dehydrogenase I (11β-HSD1) activity in an adult rat model. Alleviating 11β-HSD1 activity is therefore a logical and common way to treat hyperadrenalism. PF915275 (PF; 4'-cyano-biphenyl-4-sulfonic acid (6-amino-pyridin-2-yl)-amide) is a selective inhibitor for 11β-HSD1. This study aimed to determine whether PF915275 could alleviate the hyperadrenalism induced by NP. In addition to a rat model, the effects of NP and PF915275 were measured in human preadipocytes. Methods For the in vivo rat model, female adult rats exposed to NP during the developmental period were divided into two treatment groups, with one receiving oral DMSO solution and the other receiving PF915275 once per day for 4 weeks. After the final treatment, the rats from each group were sacrificed for analysis. For the in vitro human model, human preadipocytes received 2 regimens of NP treatment. One treatment regimen occurred before differentiation (to mimic the sensitive developmental period; P exposure), and the other included continuous exposure from preadipocytes to fully differentiated adipocytes (to mimic the growing and adult periods, respectively; C exposure). Protein and RNA were extracted from rat tissues and the preadipocytes for western blot and real-time PCR analysis. Results In the rat model, PF915275 alleviated NP-induced effects by interfering with adipogenesis pathways, including enhancing PPARα expression, decreasing PPARγ expression, and reducing both 11β-HSD1 protein and mRNA expression levels. Additionally, PF915275 reduced the effects of the adrenal corticoid synthesis pathway by reducing StAR expression and 11β-hydroxylase and aldosterone synthase activities. With short-term exposure, NP enhanced PPARγ and FASN mRNA expression levels and reduced PPARα expression, whereas PF915275 alleviated these effects. With C exposure, the NP-induced accumulation of intracellular lipids was reduced by PF915275 treatment, which was mediated by decreased PPARγ mRNA and protein expression levels and increased PPARα protein expression. Conclusions The effects of NP and PF915275 treatment in both rat and human cell models are similar. Rats may be an appropriate model to study the effects of NP in humans, especially during the developmental period.